Influence of Tourism Destination Products and Images on Tourist Visiting Decision to Kota Seribu Sungai Banjarmasin - Devin Cahya Triansya; Beta Budisetyorini (Sekolah Vokasi, Universitas Gadjah Mada, 2018)
AbstractThe continuous rapidly growth of tourism sector with the tight competition in the field of tourismmakes not all tourist destinations in the world always experience an increase in the number of tourist visits each year. Banjarmasin City, dubbed the “Kota Seribu Sungai” or